Metody oceny jakości odwzorowania współwystąpień kategorii cech w analizie korespondencji - Stanimir, Agnieszka (Methods of Quality Measurement in Displaying Relations Between Categories of Variables in Correspondence Analysis, 2007)
Article presents methods of quality measurement in displaying relations between categories of variables in correspondence analysis. This problem is very important, because analysis' results are usually presented in less than full dimensional space. Diagnosis of range of information lost while displaying relations between categories of variables plays important supporting role in the interpretation of results of correspondence analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 186-194